PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS VII MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Fadhilla, Putri; Rahmasari, Eka; Budi Rahaju, Endah; Syamsiah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the improvement of student learning outcomes at SMP Negeri 8 Kediri through the Problem Based Learning (PBL) model in Mathematics instruction. This type of research is Classroom Action Research (CAR). The study focuses on the PBL model and student learning outcomes. The subjects of this research are 31 students of class VII G at SMP Negeri 8 Kediri. Data collection techniques were carried out through tests to measure student learning outcomes during the application of the PBL model. The research results showed a significant increase in learning outcomes and learning interest from the initial conditions to cycle II after using PBL. Learning outcomes in cycle II reached the determined success indicator, which increased to 74% from the pre-cycle rate of only 36%. In cycle I, the students' learning outcomes increased to 49%, and in cycle II, they increased further to 74%. This improvement indicates the successful implementation of the PBL model, thus it can be concluded that the application of the PBL model is effective in enhancing students' mathematics learning outcomes.